Analisis Faktor-Faktor yang Mempengaruhi Tindak Lanjut Hasil Audit oleh Inspektorat Daerah: (Studi Empiris Pada SKPD Provinsi Maluku) - Dirk Berly Tehuayo; Audry Leiwakabessy (Jurnal Administrasi Terapan, 2025)
This study aims to identify and analyze the factors influencing the follow-up of audit findings conducted by Regional Inspectorates. The main focus lies on four independent variables: auditor competence, quality of audit recommendations, commitment of SKPD (Local Government Work Units) leadership, and the effectiveness of internal control systems. A quantitative approach was used through a survey method involving 100 respondents from various SKPDs. Data were analyzed using multiple linear regression. The results indicate that all four variables significantly influence audit follow-up simultaneously, with a determination coefficient (R²) of 0.72. Partially, the quality of audit recommendations and leadership commitment emerged as the dominant factors driving follow-up actions. These findings highlight the importance of enhancing auditor competence, developing high-quality recommendations, fostering committed leadership, and strengthening internal control systems to support accountable and effective governance. Keywords: Audit Follow-Up, Auditor Competence, Recommendation Quality, Leadership Commitment, Internal Control System